Structural Determinants of Green Growth: The Role of Institutions (KASBIT Business Journal, 2026)
The purpose of this research is to estimate the effects of structural determinants on green growth (GG) in developing economies, considering the moderating effects of institutional quality (IQ). A balanced panel dataset of ninety-six developing countries from 2004 to 2023 was used and robust panel-regression techniques were employed to estimate relationships. Findings show that foreign direct investment (FI), financial development (FD), urbanization (UG), and human capital (HC) significantly undermine GG, while population growth (PG) has a significant positive impact on GG in sample economies.  Moreover, IQ is found to have mixed effects: its direct effect on GG is significantly negative, while its moderating impact is positive in the cases of FD and UG, implying that strong institutions may redirect financial and urbanization dynamics towards sustainability. Conversely, the findings show that IQ does not moderate the impact of FI, PG, and HC, indicating institutional constraints in channeling structural drivers towards GG. Furthermore, the findings also reveal a nonlinear IQ effect, suggesting that GG increases once IQ goes beyond a certain threshold. In sum, the study emphasizes that, in the absence of strong IQ, structural and developmental determinants may weaken GG in developing economies. The results provide useful policy insights such as the need for institutional reforms, focused-green financing, and education for sustainable development to ensure a real transition towards GG.
Keywords: Green Growth; Foreign Direct Investment; Urbanization; Population Growth; Institutional Quality; Financial Development; Human Capital